Differences in Grand Slam competition statistics between professional and U-18 players according to the sex. [Diferencias en las estadísticas de competición de Grand Slam entre jugadores profesionales y Sub-18 según el género]. - Angel Iván Fernández-Garcia; Jose Maria Gimenez-Egido; Gema Torres-Luque (Ramón Cantó Alcaraz, 2021)
The aim of the study was to determine the differences in competition statistics between professional and under-18 (U-18) players by sex. A total of 546 official matches of Grand Slam were selected (268 male and 278 female). The data was obtained from the official website of the tournaments. Different variables related to match time, serve, return and winners-unforced errors were analysed. Descriptive analysis and a Mann-Whitney U test to analyse the differences between professional players and U-18 players were performed. Likewise, to estimate which variables obtained the greatest significant differences was conducted a discriminant analysis. ATP players played longer sets and matches, had a better serve performance and hitting more winners than U-18 male players. Junior male players increased their return effectivity and hit fewer unforced errors than ATP players (p< 0.001). WTA players hit less double faults, had a better percentage of first serve-in and hit more winners than U-18 female players. Junior female hit less unforced errors than WTA players (p< 0.001). Moreover, the key differences between professional and junior players both males and females were the number of winners and unforced errors per set. Further, the match time and aces hitting were key factors that differentiated ATP players from U-18 male players. These data would be help coaches to design junior's trainings programs, improving their performance based on key professional stage factors.